The Impacts of Hong Kong's Currency Board Reforms on Its Interbank Market - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2003)
Among the economies with a Currency Board System (CBS), Hong Kong (HK) is probably the one with the largest and most developed financial sector, as well as the highest capital mobility. Hence, studying HK’s CBS is not only crucial to HK, but also important for the understanding of the modern CBS. This paper outlines the major monetary reforms in HK since the late 1980s. The impacts of these reforms and the 1997–1998 Asian Financial Crisis are then examined empirically. We focus on the differentials between the US and HK interbank interest rates. We assume the conditional-mean equation follows an autoregressive process and the conditional-variance equation follows a generalized autoregressive conditional heteroscedasticity process. This model captures the time-varying level and volatility of the differential. In light of the empirical results we provide an assessment of the reforms in HK.